PUBLIC RELATIONS IN THE DIGITAL ERA: CASE STUDY OF THE USE OF SOCIAL MEDIA BY GOVERNMENT PUBLIC RELATIONS IN ANRI - Kharisma, Tiara; Kurniawan, Firman (Jurnal InterAct, 2018)
In the digital era, public organizations are inevitably required to adapt interactions with the public and manage information through online communication. This activity became one of the tasks carried by government public relations (PR). The objective of this research describes how the use of micro-level social media in public organizations to achieve PR objectives. The research locus is the National Archives of the Republic of Indonesia (ANRI). The research method used is qualitative. Data were collected through interviews and document studies. The result indicates that micro social media has been used ANRI since 2014, namely: Twitter and Facebook. In managing of social media, it is found that the PR model is asymmetric, the PR strategy is dominated by the proactive strategy with transparent communication type. The reactive strategy used deliberate inaction strategy. Social engagement in social media is still considered minimal. There is some information content that has significant attention, which is considered to have relevance to current issues, humanist and has a high historical value. PR in ANRI have realized the importance of managing social media and communication models that should be implemented, but in reality, hasn't been able optimally. This is because there are obstacles related to the organization policy, the capacity of social media managers.